#TITLE_ALTERNATIVE# - DWITAMA (NIM 15106038), BOY
Identify the variables that affect the vulnerability of coastal categorizing two variables, physical variables and non-physical variables (socioeconomic). Physical variables consisted of maximum tidal range, maximum current speed, significant wave height, the slope of the topography, sediment type, land cover, rainfall intensity, maximum wind speed, and direction of coming waves while the non-physical variables are the population density, the number of labor force, the economic value of land, the value of land productivity, GDRP, and the rate of population growth. Then classified and weighted by the AHP method to each of these variables to create a model of coastal vulnerability index in Cirebon. Based on the research results, 4 (four) sub-districts of Cirebon coastal area belong to the category are susceptible to physical variables and there are 7 (seven) sub-districts of Cirebon coastal area that get into the category of very vulnerable to socioeconomic variables.